Razvoj profila gledališkega in opernega režiserja na Slovenskem med obema vojnama - Koter, Darja (Muzikološki zbornik, 2010)
The article deals with the development of opera directing and director's profile in Slovenia between the two wars, taking into consideration Opera and Theatre in Ljubljana. The author states specific influences of theatre directing upon the development of Opera, as well as the interaction with European movements, and treats the most distinguished personalities in the domain of opera directing in Ljubljana.
Keywords: Debevec, Ciril, 1903-1973; gledališka režija; Kreft, Bratko, 1905-1996; Ljubljana Drama theatre; Ljubljana Opera theatre; ljubljanska Drama; ljubljanska Opera; opera direction; operna režija; Šest, Osip, 1893-1962; theatre direction